Penerapan Metode Drill untuk Meningkatkan Keterampilan Membaca Al-Qur’an Siswa Madrasah Diniyah Syekh Subaqir - Fitri Rahmawati; Ibnu Muchlis (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study evaluates the application of the drill method in improving Qur'an reading skills in grade 4 students at Madrasah Diniyah Sheikh Subaqir Sukorejo. The drill method, which involves repeated and intensive practice, was applied to improve students' reading accuracy, speed, and understanding of tajweed rules. This study used a descriptive qualitative approach with data sources from 12 students. The results showed that the drill method significantly improved students' Qur'an reading skills, with clear improvements in reading accuracy and student motivation. Supporting factors such as student enthusiasm and parental support contributed to the success of the method, while inhibiting factors included inappropriate practice time and lack of encouragement. The findings underscore the importance of the drill method in Qur'ānic teaching and contribute to the development of more effective teaching strategies in similar educational institutions.